Examining Indonesian Stock Price Movement Amid COVID-19 Pandemic: Which Sectors that Underperformed the Most? - Fakhrunnas, Faaza; Ramadhani, Almadita (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractThe stock market is a financial market that is highly responsive to changes in economic conditions. Therefore, the stock market normally reflects the current economic conditions. This study discusses the effect of the COVID-19 pandemic on the Indonesian stock exchange in several industrial sectors. Using the event study method, this study utilized a time-series data over a five-month period starting from December 2019 to April 2020. To examine the short-run and long-run impact among the observed variables, this study also applied the ARDL (Autoregressive Distributed Lag). The findings showed that the COVID-19 pandemic affected stock performance, particularly in trade, service and investments, and agricultural sectors, all of which experienced a negative return on the day of the first announcement of the COVID-19 positive cases. In addition, the outbreak evidently influenced the cumulative abnormal return in the short run, but not in the long run. Keywords:Stock Market, COVID-19 pandemic, Event Study, ADRL, Cumulative Abnormal Return